(untitled) (Hackensack, N.J., 2005)
This volume contains a valuable collection of research articles by active and well-known mathematicians in differential geometry and mathematical physics, contributed to mark Professor Kouei Sekigawa's 60th birthday. The papers feature many new and significant results while also reviewing developments in the field. The illustrious career of Professor Sekigawa and his encounters with friends in mathematics is a special highlight of the volume.
Keywords: Geometry, Differential,Mathematical physics